Material no estructurado y las relaciones lógico matemáticas en niños del nivel de preparatoria en la Escuela de Educación Básica Pompilio Reinoso Jaramillo de la ciudad de Loja, periodo 2022 - 2023 - Quizhpe Abrigo, Elsa Verónica (2023)
Logical-mathematical relationships are cognitive processes that the child explores and understands based on the connections they have with the elements of their environment to enhance different aspects such as: classification, serialization, correspondence, counting, colors, geometry, among others. The present investigation allowed us to determine the incidence of unstructured material for strengthening logical-mathematical relationships in children at the high school level at the Pompilio Reinoso Jaramillo Basic Education School in the city of Loja, period 2022 - 2023. It was worked under a design quasi-experimental, with a mixed approach that made it possible to investigate clear and precise information, quantitatively for the collection and analysis of numerical data and qualitatively for the interpretation of the activity guide; In addition, the following methods were used: inductive-deductive to give meaning and order to the work, and the analytical-synthetic method that allowed an individual analysis of the variables. To collect information, the EVAMAT-0 test was used as an evaluation instrument, applied to twenty-five children, which allowed analyzing aspects such as: geometry, quantity-counting, and problem solving; obtaining that, 73% of the children were at a low level, 19% at a medium level, and 8% at a high level, after the implementation with an activity guide based on unstructured material, the difficulties were reduced, having, 10% were at a low level, 35% at a medium level and 55% reached a high level. Concluding that the impact of unstructured material with its typology: recycled, from the natural and everyday environment, allowed the acquisition of basic contents such as: recognizing colors, identifying figures, associating number-quantity, performing simple additions and subtractions, given that they are accessible and manipulative didactic resources enhanced logical-mathematical relationships, thus contributing to critical thinking. Keywords: Logical mathematics, manipulation, unstructured material, cognitive processes, pedagogical resource.